Learn Objective-C on the Mac For OS X and iOS - Knaster, Scott; Dalrymple, Mark; Malik, Waqar (Apress : Imprint: Apress, 2012)
Learn to write apps for some of today's hottest technologies, including the iPhone and iPad (using iOS), as well as the Mac (using OS X). It starts with Objective-C, the base language on which the native iOS software development kit (SDK) and the OS X are based. Learn Objective-C on the Mac: For OS X and iOS, Second Edition updates a best selling book and is an extensive, newly updated guide to Objective-C. Objective-C is a powerful, object-oriented extension of C, making this update the perfect follow-up to Dave Mark's bestselling Learn C on the Mac. Whether you're an experienced C programmer or you're coming from a different language such as C++ or Java, leading Mac experts Scott Knaster and Waqar Malik show how to harness the power of Objective-C in your apps! A complete course on the basics of Objective-C using Apple's newest Xcode tools An introduction to object-oriented programming Comprehensive coverage of new topics like blocks, GCD, ARC, class extensions, as well as inheritance, composition, object initialization, categories, protocols, memory management, and organizing source files An introduction to building user interfaces using what is called the UIKit A primer for non-C programmers to get off the ground even faster.